Evaluating the Hydraulic Performance of Existing Water Supply Distribution System: The Case of Tebela Town of Wolaita Zone, Southern Ethiopia - Tefera, Zerihun Tefera; Mhiret Dananto (International Journal of Advanced Multidisciplinary, 2022)
The adequate and reliable water supply in the developing towns of Ethiopia is becoming a challenge for most water utilities especially public service providers like Tebela town. The main objective of this research was to check the hydraulic performance of Tebela town's water distribution system by evaluating water demand and production, losses of water, and hydraulic parameters. Both secondary and primary data sources were used for this study. Primary data was collected through field surveys and photographs of relevant sites and infrastructures. The secondary data was collected from design documents, literature, journals, and office. Moreover, to analyse the existing water distribution system, a model was developed by using WaterGEMSv8i software. The model simulation run was performed for peak and low demand scenarios to analyze the distribution system. The analysis shows that the water supply coverage was 25.9%. The water loss of the town was 17.2% from the total water production. Modeling results showed violation of maximum and minimum pressure and velocity criteria at different junctions and pipes. After modifying the existing water distribution system, 96.23% of the junctions are in the recommended pressure range and 73.50% of the pipes are in the recommended velocity range at minimum hourly consumption. Generally the result of the analysis shows that the overall hydraulic performance of water distribution of the town was moderate, which is reflected by medium water production rate, water consumption, and nonrevenue water, also low water coverage, some velocity and pressure is not in permissible range. Therefore, it is important to rehabilitate and improve the water distribution system capacities, establish pressure zones, increase pumping rates, and drill additional boreholes to meet the current water demand and future demand.